The outcomes of intra-articular injection of tranexamic acid in arthroscopic anterior cruciate ligament reconstruction: a systematic review - Pramana, Made Ramanda B.; Aryana, I. Gusti N. Y. B.; Widyananda, Gede A. D.; Aryana, I. Gusti N. W.; Wiradiputra, Agus E.; Giri, Kadek G. B. (International Journal of Advances in Medicine, 2025)
Arthroscopy is the gold standard for anterior cruciate ligament (ACL) rupture nowadays. Although minimal invasive, this procedure carries the risk of hemarthrosis. Hemarthrosis and pain can interfere with the patient’s rehabilitation process and can develop into arthrofibrosis. The administration of antifibrinolytic agents such as tranexamic acid (TXA) has long been developed but it had various results. Compared with intravenous administration, intra-articular (IA) injection of TXA in ACL reconstruction cases is still rarely done. The purpose of this study was to assess the outcomes of intra-articular administration of TXA in ACL reconstruction cases. Identification of relevant studies was developed with a comprehensive search strategy. The eligibility of each study was assessed based on predetermined inclusion and exclusion criteria. The inclusion criteria were studies that discussed the outcomes of giving IA TXA in ACL reconstruction, randomized controlled trial study design comparing IA TXA with control, and full-text English-language journals from 2019-2024. IA administration of TXA is given immediately after the arthroscopy procedure. This systematic review was conducted in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA). Four studies comprising 550 patients who were treated with IA TXA were included. Assessed from postoperative bleeding, patients who underwent IA TXA tended to have less bleeding than the control group with most studies showed a significant difference in the amount of bleeding (<0,05). Most studies represented that administration of IA TXA was able to significantly reduce postoperative pain. No patients presented with systemic side effects or complications such as infection, deep vein thrombosis, retears, or revisions through the administration of this procedure. IA administration of TXA can be considered as a safe modality with good tolerance to overcome bleeding or pain in ACL patients undergoing arthroscopy.